"PRESERVATION OF INTANGIBLE CULTURAL HERITAGE: TRADITIONS, LANGUAGES, AND PRACTICES" (Proceedings of International Educators Conference, 2024)
The preservation of intangible cultural heritage (ICH) presents a multifaceted challenge in the modern world, where globalization and technological advancements continually reshape cultural landscapes. This thesis explores the complexities and strategies involved in safeguarding traditions, languages, and practices that constitute the essence of cultural identity. It delves into the significance of ICH as a repository of collective memory, creativity, and social cohesion, emphasizing its dynamic nature and adaptive resilience in the face of contemporary pressures.The thesis examines various dimensions of ICH preservation. It investigates the roles of communities, individuals, governments, and international organizations in protecting and promoting ICH at local, national, and global levels. Special attention is given to the role of digital technologies in documenting, disseminating, and revitalizing endangered languages and traditions, while also exploring the ethical considerations and challenges inherent in digital preservation.